Synthesis of Struvite Crystal (MgNH4PO4.6H2O) from Laundry Waste to Consider its Potential as a Plant Fertilizer: Stirring and Processing Temperature Effect - Nur Aini Fauziyah; Dyah Suci Perwitasari; Pardi Sampe Tola (The Journal of Pure and Applied Chemistry Research, 2022)
This paper aimed to process phosphate from laundry waste to be struvite crystal by precipitation and crystallization methods. In general, phosphates are difficult to remove by conventional treatment technologies. Therefore, precipitation and crystallization methods can be an alternative choice for phosphate recovery. Precipitation and crystallization methods can serve to remove dissolved phosphate content in wastewater, as well as convert it into a solid form that can be reused as industrial raw materials. The research variables used were stirring temperature (25, 30, and 35 °C) and stirring speed (100, 125, 150, and 200 rpm). By using X-ray Fluorescence (XRF) and Scanning Electron Microscope (SEM-EDX), the analysis showed that the highest percentage of phosphate removal was at a stirring speed of 100 rpm at 30°C, which was 47.5%. X-ray Diffraction (XRD) was also carried out on several samples and it was confirmed that the dominant crystal phase formed was a struvite (MgNH4PO4.6H2O) for all samples, and secondary phase Magnesium Phosphate Hydrate (Mg3(PO4)2*8H2O was found in a stirring speed of 100 rpm at 30°C. The morphology of the struvite crystals formed resembles irregular flakes by using SEM.